A New Approach to Evaluating Trade Policy - Anderson, James E.; Neary, J. Peter (Review of Economic Studies, 1996)
This paper introduces a new index number, the Trade Restrictiveness Index, which measures the restrictiveness of a system of trade protection. The index is a general equilibrium application of the distance function and answers the question: “What uniform set of trade restrictions is equivalent (in welfare terms) to the initial protective structure?” The index is applicable to both tariffs and quotas and permits international and intertemporal comparisons. The index is operational and we provide two empirical examples to illustrate its applicability and to show its superiority to commonly used measures.